Sensory evaluation and consumer acceptability of zinc biofortified rice by farm women in Telangana, India - Waris, Amtul; Neeraja, Chirravuri Naga; Azam, Mohammed Mohibbe; Jangaiah, Battu (Journal of Cereal Research, 2021)
Most of the Indian diets are typically based on cereals and lackmicronutrient-rich vegetables, fruits, and flesh foods. The incorporationof zinc biofortified rice in daily diets can help overcome zinc deficiency.The present study aimed to analyze the consumers’ acceptance of zincbiofortified rice as the willingness of consumers to accept it is importantfor the success of biofortification strategy to combat micronutrientmalnutrition. The consumers’ acceptance of zinc biofortified rice interms of its hand feel mouth feel texture, taste, and overall acceptabilitywas determined using the Five-point Hedonic scale. Hand-poundedsamples of zinc biofortified rice and control were provided to sixtyfarm women to evaluate by the Home Use Test protocol. The index ofacceptability (IA) was worked out for the acceptance of zinc biofortifiedrice and was found to be greater than 70% for all the parameters. Theconsumers’ socio-economic characteristics did not show a significantrelationship with the acceptability of zinc biofortified rice except forhand feel texture. Based on the hedonic categorization suggested byBelmes (2019), the overall acceptability of both the zinc biofortifiedrice and control are in the acceptable category of hedonic rating.Therefore it can be concluded that the zinc biofortified rice varietyDRR Dhan 45 is equally acceptable to the consumers as the controlrice. The consumers’ socio-economic characteristics did not show asignificant relationship with the acceptability of zinc biofortified rice.The zinc biofortified rice can be promoted for use in daily diets tohelp meet the zinc needs of the family and included in the nutritionintervention programs of the country for overcoming micronutrientmalnutrition.